A Domino One-Pot Approach to Functionalized Benzonitriles from 2-[(3-Hydroxy/acetoxy)propyn-1-yl]benzamides - Nair, Sindoori R.; Chinta, Bhavani Shankar; Baire, Beeraiah (Synthesis, 2024)
Functionalized benzonitriles, α,β-epoxyketones and β-hydroxy-α-haloketones are found in numerous medicinally important molecules, whilst benzonitriles in combination with any of these functional groups may be of interest to medicinal chemists. However, the simultaneous incorporation of a nitrile group and these functional groups on the aromatic ring is a challenging task. Herein, we report a strategy for the rapid and simultaneous construction of structurally novel benzonitrile derivatives, possessing either an ortho-α-iodo-β-hydroxyketone, an α,β-epoxyketone or an α,β-enone, from unprotected, 2-[(3-hydroxy/acetoxy)propyn-1-yl]benzamides. This process involves NXS-promoted dehydration–halohydration followed by DIPEA-mediated epoxide formation (from alcohols). We have developed both stepwise and one-pot strategies to improve the synthetic efficiency. No metal catalyst is employed and the method exhibits good substrate scope and yields.
Keywords: 2-(alkynyl)benzamides; benzonitriles; α,β-epoxyketones; α-halo-β-hydroxyketones; one-pot approach